Simulation and analysis of water concentration in the proton exchange membrane. (2015) - Chen, Shizhong; Xia, Zhongxian; Xing, Shiyu; Zhang, Xuyang; Wu, Yuhou
Water content in proton exchange membranes (PEM) has an important effect on PEM fuel cells. The water concentration gradient map was simulated by using COMSOL multiphysics, and this figure was calculated and analysed to get the water concentration distribution in PEM. The results show that water concentration in the membrane shows inverse parabolic increase along the direction of gas flow. The trend of water concentration on the cathode surface is the same as on the anode surface, both of them increase along the direction of gas flow, but the value on the cathode side is higher than that on the anode side. The change rate of water concentration on the membrane increases along the direction of gas flow. The water concentration on the middle position of the membrane is the lowest throughout the membrane, even lower than inlet along the thickness direction, which can lead to water shortages.